2005
DOI: 10.1111/j.0013-0133.2005.00970.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental Leave and Child Health Across OECD Countries

Abstract: To understand the relationship between parental leave and child health better, this study examines the aggregate effects of parental leave policies on child health outcomes using data from 18 OECD countries1 from 1969–2000. The focus is investigating the effects of both job‐protected paid leave and other leave – including non‐job‐protected paid leave and unpaid leave – on child health outcomes, more specifically, infant mortality rates, low birth weight and child immunisation coverage. This study explores the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
196
0
10

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(218 citation statements)
references
References 12 publications
12
196
0
10
Order By: Relevance
“…In addition, paid maternity leave was associated with a statistically signicantly lower probability of having a low birth weight child, but did not aect the probability of immunisation against measles and diphtheria-tetanus-pertussis (DTP). Tanaka (2005) found no statistically signicant eects of other types of leave (i.e., unpaid leave and other leave that was not job-protected) on infant mortality. On the contrary, using policy data for 185 UN member countries, Daku et al (2012) found that full-time equivalent weeks of maternity leave is associated with higher probability of childhood vaccination rates.…”
Section: Parental Leave and Child Healthmentioning
confidence: 73%
See 1 more Smart Citation
“…In addition, paid maternity leave was associated with a statistically signicantly lower probability of having a low birth weight child, but did not aect the probability of immunisation against measles and diphtheria-tetanus-pertussis (DTP). Tanaka (2005) found no statistically signicant eects of other types of leave (i.e., unpaid leave and other leave that was not job-protected) on infant mortality. On the contrary, using policy data for 185 UN member countries, Daku et al (2012) found that full-time equivalent weeks of maternity leave is associated with higher probability of childhood vaccination rates.…”
Section: Parental Leave and Child Healthmentioning
confidence: 73%
“…Ruhm (2000) also did not examine the eect of types of parental leave other than paid/job-protected parental leave. Tanaka (2005) extended the work of Ruhm (2000) to include the USA and Japan and updated the data set from 1994 to 2000. The author examined health outcomes other than the mortality rate and controlled for other social policies that were in eects during the study period and might also aect child health.…”
Section: Parental Leave and Child Healthmentioning
confidence: 99%
“…Although paternal leave is a growing phenomenon in some countries, including Sweden, it was of minor importance for the cohorts studied in this paper and remains a marginal phenomenon in most countries today. 4 See Berger et al (2005), Gregg et al (2005), Ruhm (2000) and Tanaka (2005). 5 See Parcel and Menaghan (1994) or Moore and Driscoll (1997).…”
Section: Introductionmentioning
confidence: 99%
“…Where impact research does exist the focus has been mainly on the effects of maternity leave provision with several studies showing child health benefits for instance in immunization uptake and employment retention (Tanaka 2005;Han et al 2009). Positive health gains for children are maximized when the maternity leave is: paid, provided in a job secure context and with a duration of at least 10 weeks.…”
Section: What Is Known About Fathers Taking Leave and Fathersmentioning
confidence: 99%